ANALISA DIMENSI PELAYANAN BUTLER DALAM MELAYANI TAMU VIP PADA HOTEL X - Fisya Belda Andini; Ervina Nur Amaliasari (LPPM and Travel Operation Department Universitas Asa Indonesia, 2020)
Butlers who have the task of providing satisfying, maximum service and can meet the needs of guests, especially VIP guests, such as preparing work tool and equipment, displaying professional Butler Room standards, preparing, serving and storing food and drinks, cleaning and arranging beds and room equipment, Safeguarding guests' belongings and activities and Organizing guests. Problems can occur from Butler service, which causes complaints from guests. This study aims to determine the service standards of Butler Service and the dimension aspects of service quality at Hotel X. The method used by the author in this study is descriptive research method, while the data collection techniques used are observation, interviews, questionnaires and literature study. Quality of service or how far the difference is between the reality and expectations of guests for the servants they receive or receive. From the five dimensions of Butler's service quality dimensions, the aspects of the service quality dimension of Empathy and tangible were considered good by guests, while Assurance, reliability and responsiveness were considered to be less good.